Diagnostic utility of a targeted next-generation sequencing gene panel in the clinical suspicion of systemic autoinflammatory diseases: a multi-center study - Karacan, İlker; Balamir, Ayşe; Uğurlu, Serdal; Aydın, Aslı Kireçtepe; Everest, Elif; Zor, Seyit; Önen, Merve Özkılınç; Daşdemir, Selçuk; Özkaya, Ozan; Sözeri, Betül; Tufan, Abdurrahman; Yıldırım, Deniz Gezgin; et al. (Springer Science and Business Media LLC, 2019)
Systemic autoinflammatory diseases (sAIDs) are a heterogeneous group of disorders, having monogenic inherited forms with overlapping clinical manifestations. More than half of patients do not carry any pathogenic variant in formerly associated disease genes. Here, we report a cross-sectional study on targeted Next-Generation Sequencing (NGS) screening in patients with suspected sAIDs to determine the diagnostic utility of genetic screening. Fifteen autoinflammation/immune-related genes (ADA2-CARD14-IL10RA-LPIN2-MEFV-MVK-NLRC4-NLRP12-NLRP3-NOD2-PLCG2-PSTPIP1-SLC29A3-TMEM173-TNFRSF1A) were used to screen 196 subjects from adult/pediatric clinics, each with an initial clinical suspicion of one or more sAID diagnosis with the exclusion of typical familial Mediterranean fever (FMF) patients. Following the genetic screening, 140 patients (71.4%) were clinically followed-up and re-evaluated. Fifty rare variants in 41 patients (20.9%) were classified as pathogenic or likely pathogenic and 32 of those variants were located on the MEFV gene. We detected pathogenic or likely pathogenic variants compatible with the final diagnoses and inheritance patterns in 14/140 (10%) of patients for the following sAIDs: familial Mediterranean fever (n = 7), deficiency of adenosine deaminase 2 (n = 2), mevalonate kinase deficiency (n = 2), Muckle-Wells syndrome (n = 1), Majeed syndrome (n = 1), and STING-associated vasculopathy with onset in infancy (n = 1). Targeted NGS panels have impact on diagnosing rare monogenic sAIDs for a group of patients. We suggest that MEFV gene screening should be first-tier genetic testing especially in regions with high carrier rates. Clinical utility of multi-gene testing in sAIDs was as low as expected, but extensive genome-wide familial analyses in combination with exome screening would enlighten additional genetic factors causing disease.
Keywords: Male; Genetic testing; genetic association; lpin2 protein; autoinflammatory disease; pyrin; molecular pathology; Agammaglobulinemia; middle aged; genetics; cytoskeleton protein; Child; next generation sequencing; adult; Sequence analysis; adenosine deaminase deficiency; High-Throughput Nucleotide Sequencing; clinical trial; cryopyrin; Phosphotransferases (Alcohol Group Acceptor); priority journal; SLC29A3 protein, human; Child, Preschool; Majeed syndrome; Intercellular Signaling Peptides and Proteins; Mefv Gene; card14 protein; heredity; DNA sequence; signal transducing adaptor protein; interleukin 10 receptor alpha; tmem173 protein; Article; cross-sectional study; inheritance; Humans; human; CINCA syndrome; Genetic Testing; infancy; congenital dyserythropoietic anemia; mevalonate kinase; Calcium-Binding Proteins; Hereditary Autoinflammatory Diseases; Immunologic Deficiency Syndromes; Pyrin; major clinical study; pstpip1 protein; adenosine deaminase; Cytoskeletal Proteins; multicenter study; Severe Combined Immunodeficiency; Mevalonate Kinase Deficiency; genomic DNA; Adenosine Deaminase; systemic disease; NLRC4 protein, human; preschool child; slc29a3 protein; familial Mediterranean fever; genetic variability; Hereditary autoinflammatory diseases; hereditary periodic fever; pathogenicity; PSTPIP1 protein, human; Anemia, Dyserythropoietic, Congenital; nucleoside transporter; child; ada2 protein; osteomyelitis; vascular disease; Osteomyelitis; genetic screening; severe combined immunodeficiency; Middle Aged; unclassified drug; Familial Mediterranean Fever; female; young adult; sting associated vasculopathy; Female; caspase recruitment domain signaling protein; diagnostic value; Sequence Analysis; onset age; Adult; nlrc4 protein; Adolescent; MEFV gene; Nucleoside Transport Proteins; high throughput sequencing; Young Adult; male; mevalonate kinase deficiency; Muckle Wells syndrome; follow up; mvk protein; signal peptide; phosphotransferase; Adaptor Proteins, Signal Transducing